5 - L’appui de la France à la Réforme de l’Enseignement supérieur (ES) au Maroc : quelles finalités et quels enjeux ? - Abdelfettah Benchenna, (Journal of Higher Education in Africa, 2009)
The objective of this contribution is to try to identify the purposes of the interest shown by France in supporting the ongoing reform of the Higher Education (HE). While contextualizing this enterprise on both sides, the author attempts to show that this support: • Is part of a broader policy, called cooperation policy with Francophone countries of the South.This action, on the one hand, enables France to strengthen its international position, by forming around itself allies consisting mainly of its former colonies and, on the other, to play the role of a “translator” of European orientations, in terms of education and training, with partner countries of Europe. • Is not an end in itself but a means to introduce the logics of rationalization and commodification increasingly promoted in the educational systems of developed countries. Such an orientation somewhat displeases Moroccan decision-makers inclined to take the HE out of a crisis that it has been experiencing since the early 80s.